How to design the ask?: Funding units vs. giving money - Diederich, Johannes; Epperson, Raphael; Goeschl, Timo (AWI discussion paper series, 2021)
Charities frequently deviate from the standard donation scheme in which potential donors are asked how much money they are willing to give. Instead, they ask donors to choose how many units of a charitable good (e.g. meals, bed nets, or trees) to fund at a given unit price. In an online donation experiment, we compare the performance of such a "unit donation" scheme with that of the standard "money donation" and investigate the factors that could explain differences. We find that despite the additional demands that it imposes on the charity, the unit donation does not outperform the money donation scheme in terms of overall donations. It significantly differs, however, with respect to the propensity to give. The sign of the difference depends on the granularity of the scheme. When one unit of the charitable good is cheap, unit donation schemes increase the propensity to give and can serve as an effective tool for recruiting donors.